The impact of mannose‐binding lectin polymorphisms on lung function in primary ciliary dyskinesia. Issue 8 (22nd April 2019) - Videbæk, Katja; Buchvald, Frederik; Holgersen, Mathias Gelderman; Henriksen, Alison; Eriksson, Frank; Garred, Peter; Nielsen, Kim Gjerum
Abstract: Objective: Primary ciliary dyskinesia (PCD) is a congenital lung disease that leads to recurrent and chronic lung infection. The resulting inflammation causes lung damage and declines in lung function. Mannose‐binding lectin (MBL) is a first line host defense protein of importance for the innate immunity. Polymorphisms in the MBL gene named MBL2 result in unstable and low functional levels MBL proteins. MBL insufficiency is linked to an increased risk of lung infection and to declines in lung function in patients with cystic fibrosis. We investigated whether there is a similar link in patients with PCD. Methods: This retrospective longitudinal study included 85 patients with PCD. Diagnostics and age at diagnosis were recorded, complete spirometry data starting at diagnosis, and Pseudomonas aeruginosa infection status over the last 2 years were collected, and the patients were grouped according to MBL2 genotype status (MBL2‐sufficient or MBL2‐deficient). Results: MBL‐deficient patients were diagnosed almost 3 years earlier than MBL‐sufficient patients (median 6.1 vs 8.9 years, P   < 0.05). There were no differences in the first measured spirometry values, but MBL‐deficient patients showed greater declines in forced expiratory volume in one sec (FEV1 ) than patients with MBL sufficiency ( z ‐score: −0.049 per year [95% CI, −0.075; −0.021] vs −0.009 per year [95% CI, −0.033; 0.015]; P = 0.023). No differences were found in forced vital capacity (FVC), FEV1 /FVC, or infection status. Conclusion: MBL‐deficiency, which is associated with MBL2 mutations, was associated with a lower age at diagnosis and with steeper declines in FEV1 in patients with PCD. This suggests that the MBL genotype might be a disease modifier in PCD.